Records Keeping and Financial Performance in Local Government: A Case Study of Rubanda District Local Government. - Birungi, Edinah (Kabale University, 2024)
The study was about Records Keeping and Financial Performance in Local Government: a case study of Rubanda District Local Government. It was guided by specific objectives which included; investigating the role of record keeping on the financial performance of Rubanda district local government. identifying the challenges of record keeping on the financial performance of Rubanda District Local Government, proposing possible solutions to the challenges of record-keeping On financial performance in Rubanda District Local Government. The study used a descriptive research design which was both qualitative and quantitative. The study used a study population of 60 respondents where 52 respondents were selected using the Krejen Morgan table. Data was collected from these respondents using a questionnaire, observation checklist, and interview guide using both purposive and simple random sampling techniques. The study findings show that the role of record keeping on the financial performance of Rubanda district Local Government was Proper accountability and improved auditing, it enables Easy monitoring, Easy control of resources, reduced waste of resources, and Improved effectiveness. Challenges facing personnel in the management of records at RDLG. More respondents identified lack of records management policy as the major challenge, lack of adequate professionally trained record managers. Other challenges stated were lack of records retention and disposition schedule/ policy. improper security for records. lack of filing manual/finding aids and inadequate storage equipment and solutions to the challenges faced in record-keeping at RDLG were the provision of retention and disposition schedule, Lack of Records management policy, Improving security for records, Employing professionally trained record Managers, provision of Filing Manual/Finding Aids and Involvement of manual operations, Training record users on modern record management practices and Installing back up facilities for ICT. The researcher further sought to find out whether the RDLG issued guidelines and procedures on the creation and capture of those records that are necessary to meet operational, fiscal, legal, and other requirements. More than half suggested procedures and guidelines did not exist concurred that the guidelines and procedures were in place. Finally, the study recommends that Urgent steps should be taken by the authorities concerned to conduct a records survey to carry out records appraisal, develop retention and disposal schedules, create records management procedures, and prepare a disaster recovery and vital records plan. Records management policy should be put in place to enhance records management activities within the Local Government. This can be done by policymakers so that the record cycle operates on a normal scale and there is a need to have standards in place to identify best practices. These standards may be record authorization, record retention, use, and disposition. This can be done by the records department and Training programs on records management organized for the staff through seminars and workshops